2023
DOI: 10.3390/children10020317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a High Intensity Interval Training (HIIT) Program on Anthropomorphic and Cardiometabolic Variables in School Children with Overweight and Obesity

Abstract: The aim of this study was to assess the effects of a high intensity interval training (HIIT) program on anthropomorphic and cardiometabolic variables in schoolchildren with overweight and obesity. A total of 443 schoolchildren (age: 6.37 ± 0.65 years) took part in this study. The experimental group (EG; n = 295; age = 6.40 ± 0.64 years) was compound with children with overweight and obesity, whereas children with normoweight were included in the control group (CG; n = 148; 6.31 ± 0.67 years). The EG performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, the HIIT program significantly reduced the number of hypertensive and prehypertensive students after the intervention. In a very recent study, Espinoza Silva et al (14), detected no changes in blood pressure after a 28-week HIIT intervention in younger students. Inconsistent results between studies may be explained by differences in the study design.…”
Section: Discussionmentioning
confidence: 92%
“…However, the HIIT program significantly reduced the number of hypertensive and prehypertensive students after the intervention. In a very recent study, Espinoza Silva et al (14), detected no changes in blood pressure after a 28-week HIIT intervention in younger students. Inconsistent results between studies may be explained by differences in the study design.…”
Section: Discussionmentioning
confidence: 92%
“…It was also found out that such workouts may be of great benefit in the improvement of body mass index and waist circumference of students [35][36][37][38]. Importantly, certain scientific papers have shown that improvements are highly successful for overweight and obese individuals after seeing the effects of multiweek HIIT, such as the TABATA workout, in both overweight young adults and those with normal body mass index and waist circumference [39][40][41][42]. Additionally, there have been recent studies that have mentioned the effectiveness of TABATA training in the virtual environment.…”
Section: Introductionmentioning
confidence: 99%